Stratigraphy and dating of a large slumping event in the Northern Aegean - LYKOUSIS, V.; ROUSAKIS, G.; PAVLAKIS, P.; ALEXANDRI, M. (Bulletin of the Geological Society of Greece, 2018)
Continuous seismic (Air-Gun) subbotom profiling in the N.Aegean was revealed a large submarine translational slide. The failure zone is extended from about 300m depth down to 800 m and covers an area of 85 Km2. The mean thickness of the slide reaches about 55 m and an estimated total volume of 4 Km3 of Quaternary sediments have been slided along a distance of 6 to 7 Km. Chronostratigraphic analysis of the acoustic reflectors imply that the slide plane is the muddy layer of late Pleistocene age (170-240 Ka BP). AMS dating of sediment cores provided indications that this major slide event occurred 5 to 6 Ka BP.